Tehnik Emphaty Dalam Cybercounseling Model Asynchronous - Lukman Nulhakim (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
Cybercounseling Asynchronous approach allows clients and counselors to communicate via text messages, emails, or other platforms without having to be at the same time. This model provides flexibility for clients to access services at any time and allows counselors to respond according to their schedule. The Asynchronous model provides a more flexible space in its implementation, allowing service interactions not to be direct. The non-direct and textual counseling model allows for errors in understanding the guidance messages contained in the Asynchronous digital counseling model process. So in this article the author emphasizes aspects related to the content of guidance or information via text messages, emails, or other platforms that uphold the content aspect that contains the scope of empathy aspects. The study used an approach (library research) with several discussions of the findings, namely the concept of a digital counseling system with an Asynchronous model in managing BK services, including 1) Overview of cybercounseling asynchronous approach (2) Urgency of empathy content in cybercounseling asynchronous approach (3) Offering empathy techniques in cybercounseling asynchronous model.